The English Trade in Nightingales Italian Opera in Nineteenth-Century London - Zechner, Ingeborg (2017)
This books deals with the Italian opera business in nineteenth century-London. A special emphasis lies on the opera singers as the most important protagonists of the London system. This special role will be examined through the analysis of the opera audience in London, the contractual practice and the tradition of the adaptation of operas to the likes of the London market as well as the substitution of arias.